2021
DOI: 10.1155/2021/7027793
|View full text |Cite
|
Sign up to set email alerts
|

Myopic Correction with Iris-Fixated Phakic Intraocular Lenses: Twelve-Year Results

Abstract: Purpose. To evaluate a 12-year follow-up of myopic patients after iris-fixated phakic intraocular lenses (IF pIOLs) implantation. Setting. Ophthalmology Department, Military University Hospital in Prague (Czech Republic). Design. Single-center retrospective cohort study. Methods. We describe the results of a cohort study that included 85 eyes of 46 myopic patients who underwent implantation of Verisyse myopia, Veriflex, and Verisyse myopia toric (all Abbott Medical Optics, Inc.) intraocular lenses. Refractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
6

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 39 publications
0
10
1
6
Order By: Relevance
“…This factor would be important in the context mentioned in a previous study by Galvis et al, where they mentioned a possible extrinsic mechanical factor, such as ocular rubbing or ocular compression when sleeping, as a possible cause of chronic endothelial loss in these patients. [8] Nemcova et al, in their recently published study, found an inverse correlation between baseline pachymetry and endothelial cell loss with a 12-year follow-up [18]. In the present study, an association between central corneal thickness and postoperative endothelial cell loss was not detected.…”
Section: Discussioncontrasting
confidence: 51%
“…This factor would be important in the context mentioned in a previous study by Galvis et al, where they mentioned a possible extrinsic mechanical factor, such as ocular rubbing or ocular compression when sleeping, as a possible cause of chronic endothelial loss in these patients. [8] Nemcova et al, in their recently published study, found an inverse correlation between baseline pachymetry and endothelial cell loss with a 12-year follow-up [18]. In the present study, an association between central corneal thickness and postoperative endothelial cell loss was not detected.…”
Section: Discussioncontrasting
confidence: 51%
“…4,18 Secondary corneal mechanical deformation due to ocular rubbing and nocturnal ocular compression related to the sleeping position leading to possible peripheral endothelial cell loss with irisclaw phakic IOL is also noteworthy. 4,19,20 The present results demonstrated that ECD continuously decreased postoperatively in the long-term follow-up despite safe pIOL explantation without intraoperative complications, use of dispersive viscoelastics, and minimization of operation time to reduce surgical trauma. Although normal ECD declines with age at rates of 0.6% per year, 5% to 6% every 10 years, and 3.5% to 5.7% after widely performed phacoemulsification, our results indicated that ECD had decreased by more than 25% 2 years after pIOL explantation.…”
Section: Discussionmentioning
confidence: 54%
“…4,18 Secondary corneal mechanical deformation due to ocular rubbing and nocturnal ocular compression related to the sleeping position leading to possible peripheral endothelial cell loss with iris-claw phakic IOL is also noteworthy. 4,19,20…”
Section: Discussionmentioning
confidence: 99%
“…10-12 Jahren wurde bei 0-15 % bzw. 6,3-20 % der Augen ein Endothelzellverlust von ≥ 25 % im Vergleich zur präoperativen Endothelzelldichte beobachtet [21,25,26]. Die Endothelzelldichte von < 1500 Zellen/mm 2 zeigte sich bei 0,8-3,2 % bzw.…”
Section: Artisanunclassified
“…3,5-4,0 % der Augen 5 bzw. 10-12 Jahre postoperativ [21,25]. Die Ergebnisse der Langzeitstudien mit einer Beobachtungsdauer von mindestens 5 Jahren sind in der ▶ Tab.…”
Section: Artisanunclassified